2017 J. Leonard Goldner Award Winner: Synovial Fluid Composition of Inflammatory Cytokines, Matrix Metalloproteinases, and Cartilage Breakdown Products are Dependent on Time after Intra- Articular Ankle Fracture. Issue 3 (11th September 2017) - Adams, Samuel; Reilly, Rachel; Huebner, Janet; Kraus, Virginia; Nettles, Dana
Category: Ankle, Ankle Arthritis, Basic Sciences/Biologics, Trauma Introduction/Purpose: Intra-articular ankle fracture (IAF) is known to cause post-traumatic osteoarthritis (PTOA) of the ankle. While the exact etiology remains elusive, the sequelae of intra-articular inflammation has been suggested and our previous work demonstrated a highly pro-inflammatory environment at the time of IAF fixation. ORIF of an IAF can occur 10-14days, or later, after fracture, subjecting the cartilage to this pro-inflammatory environment during this time. Therefore, there is ample time to intervene with an anti-inflammatory agent, yet the exact synovial fluid (SF) composition is unknown. This study examined the effect of time and fracture severity on the SF microenvironment during the acute phase following IAF. Knowledge of the intra- articular metabolic derangement after IAF will help to understand the pathology of PTOA and to develop therapeutic interventions. Methods: Ankle SF was collected from 54 patients with an IAF at the time of surgery for initial external fixation or definitive ORIF and analyzed for concentrations of 10 cytokines, 5 matrix metalloprotienases, 2 products of cartilage catabolism, and combined products of heme metabolism. All analytes were correlated with time from fracture and further analyzed for an effect of 3 clinically relevant time subgroups that correspond to potential clinical intervention time points for ankle fracture management: 0-2 days (initial ER presentation), 3-9 days (clinic presentation), and =10 days (definitive fixation). The effect of fracture severity was determined by grouping SF according to the number of radiographic intra-articular fracture lines. Results: Correlation analysis revealed a significant relationship with time from fracture for 15 of 18 analytes (Figure 1). Temporal grouping of SF revealed an initial (0-2 days) spike of pro-inflammatory (IL-12p70, IL-1?, IL-6) and anti-inflammatory (IL-10 and IL-4) cytokines, MMP-9, and sGAG, followed immediately (3-9 days) by exposure of the joint space to heme breakdown products and an accompanying surge in mediators and products of cartilage catabolism (MMP-1, MMP-2, MMP-3, MMP-10 and CTX-II). After 10 days there was a decrease in pro- and anti-inflammatory cytokines, but a persistence of mediators of cartilage matrix catabolism. While fracture severity had a significant effect on SF levels of MMP-2, MMP-9, and CTXII, there was no clear relationship between the number of fracture lines and SF levels of analytes. Conclusion: This study provides novel insights into temporal inflammatory fluctuations following acute IAF of the ankle and supports consideration of an early evacuation of the jointspace to reduce the intra-articular inflammatory burden and exposure of the cartilage and synovium to these detrimental factors. Moreover, this study identifies the temporal composition of SF products that are known to cause osteoarthritis. Therefore, this information can be used to develop novel therapeutics that can tailored to the time of presentation after intra-articular ankle fracture.